THE INFLUENCE OF CONSUMER EXPERIENCED AND TRUST ON REPURCHASE INTENTION: A CASE STUDY OF GOFOOD USERS IN JATIWARINGIN, BEKASI CITY) - Putri, Khofifah Nabila; Abdurahman, Pangeran Syarif (Kinerja, 2025)
This study aims to analyze the influence of Consumer Experienced (X₁) and Consumer Trust (X₂) on the Repurchase Intention (Y) of GoFood users in Jatiwaringin, Bekasi City. The method used is a quantitative approach with multiple linear regression analysis and classical assumption testing. The population in this study consists of GoFood consumers in Jatiwaringin, Bekasi City. This research uses a questionnaire as the data collection tool with a sample size of 150 respondents, and the study employs the SPSS 27 program for data processing. The test results show that the data meet the classical assumptions and the regression model is significant. Consumer Experienced (X₁) (β = 0.573) and Consumer Trust (X₂) (β = 0.651) have a positive and significant effect on Repurchase Intention (Y) (Sig. < 0.05). The R² value of 0.429 indicates that both variables explain 42.9% of the variation in Repurchase Intention (Y), and the remaining 57.1% is influenced by other factors outside the model. The F-test also shows a significant simultaneous effect (F = 55.124; Sig. = 0.000). Thus, it can be concluded that Consumer Experienced (X₁) and Consumer Trust (X₂), both partially and simultaneously, have a significant impact on the Repurchase Intention (Y) of GoFood users. This model can be used as a basis for decision-making in digital marketing strategies on online food delivery platforms.